PENGARUH RELIGIUSITAS, LINGKUNGAN DAN POLA KONSUMSI TERHADAP KEPUTUSAN PEMBELIAN BUSANA MUSLIMAH MAHASISWI FAKULTAS EKONOMI DAN BISNIS ISLAM UIN DATOKARAMA PALU - Nurfitriani Nurfitriani; Rusniati Rusniati; Sappeami Sappeami (EKOBIS SYARIAH, 2023)
ABSTRACTConsumption behavior itself can be influenced by several factors both in terms of the environment, religiosity and so on. This is also the basis for consumption activities carried out by female students in fashion. This study aims to determine the effect of religiosity, environment, and consumption patterns on purchasing decisions for Muslimah female students at the Faculty of Economics and Business, UIN Palu. This type of research is field research with quantitative research methods. Data collection techniques used are questionnaires, interviews and documentation. The number of samples taken in this study were 81 respondents. The results of this study indicate that religiosity has a positive and significant effect on purchasing decisions for Muslim women's clothing with a "t" _"count" value of 3.198 > "t" _"table" 1.666 a positive beta value of 0.196 and a significance value (Sig.) 0.002 <0 ,05. The environment has a positive and significant effect on purchasing decisions for Muslimah clothing with a "t" _"count" value of 8.401 > "t" _"table" 1.664, a positive beta value of 0.630 and a significance value (Sig.) 0.000 <0.05. Consumption patterns have a positive and significant effect on Muslimah Clothing Purchasing Decisions with a value of "t" _"count" 2.844 > "t" _"table" 1.644 positive beta value of 0.200 and gain of significance value (Sig.) 0.006 <0.05. Results This study also shows that simultaneously, Religiosity, Environment and Consumption Patterns simultaneously influence the Purchase Decision of Muslimah Clothing for Students of the Islamic Economics and Business Faculty of UIN Palu. This was obtained through the F test by obtaining data with a value of "F" _"count" 85.317 > "F" _"table" 2.723 and a significance value (Sig.) 0.000 <0.05.